Language Acquisition Approach and Theory - Nabila Suci Ramadhina; Tryana Tryana; Rizky Tazkiyatul Ummami; Maharanny Setiawan Poetri; Denok Sunarsi (Peneliti.net, 2022)
This study aims to present differences of children’s abilities in acquiring language. This study uses a qualitative method by collecting sources from various journal articles and books. The object of the study is experiences that prove several theories related to language acquisition. This journal describes several language acquisition approaches which are reinforced by theories from an expert as well as examples of language acquisition experienced by the author.